We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
421
1
avatar+115 

Required:

Sum of n terms for -3n^2+2n+5

 Dec 4, 2017
edited by OldTimer  Dec 4, 2017
 #1
avatar+100168 
+3

Hi Old Timer    laugh

 

Sum of n terms for -3n^2+2n+5

 

\(\displaystyle\sum_{m=1}^n\; (-3m^2+2m+5)\\ =\displaystyle\sum_{m=1}^n\; -3m^2\quad+\displaystyle\sum_{m=1}^n2m\quad +5n\\ =\displaystyle\sum_{m=1}^n\; -3m^2\quad+\displaystyle\sum_{m=1}^n2m\quad +5n\\ \qquad\qquad \displaystyle\sum_{m=1}^n2m=\frac{n}{2}(a+L) = \frac{n}{2}(2+2n) = n(1+n)=n^2+n\\ =-3\left[\displaystyle\sum_{m=1}^n\; m^2\right]\quad+n^2+n\quad +5n\\ \text{** the next line was taken from a khan academy video which I will reference at the end.}\\ =-3\left[\frac{n^3}{3}+\frac{n^2}{2}+\frac{n}{6}\right]\quad+n^2+n\quad +5n\\ =\left[-n^3-\frac{3n^2}{2}-\frac{n}{2}\right]\quad+n^2+n\quad +5n\\ =\frac{-2n^3}{2}-\frac{3n^2}{2}-\frac{n}{2}\quad+\frac{2n^2+2n\quad +10n}{2}\\~\\ =\dfrac{ -2n^3-n^2 +11n }{2} \)

 

Khan Academy videos:

https://www.khanacademy.org/math/calculus-home/series-calc/series-basics-challenge/v/sum-of-n-squares-1

https://www.khanacademy.org/math/calculus-home/series-calc/series-basics-challenge/v/sum-n-squares-2

 

You will need to check the algebra, I could easily have made a careless mistake :)

 Dec 4, 2017

20 Online Users

avatar
avatar
avatar